Reliability of interobserver and intraobserver assessments of the Tile versus Young-Burgess classifications for pelvic ring injuries - Ruipeng Zhang; Xi Hou; Zhongzheng Wang; Siyu Tian; Junran Li; Ligeng Li; Zhiyong Hou; Yingze Zhang (Scientific Reports)
Abstract Tile and Young-Burgess classification systems have been widely used to classify pelvic ring injuries in clinical settings; however, these two systems are rarely mentioned in the literature despite their reproducibility and practical application. The purpose of this study was to assess the interobserver and intraobserver reliability of the Tile and Young-Burgess classification of pelvic ring injuries. Eight hundred seven patients with pelvic fractures who presented to two I-level trauma centres between January 2016 and June 2020 were recruited for this study. The anteroposterior, inlet, and outlet of the pelvis were observed on radiographic images, and CT scans were performed on each patient. The anteroposterior, inlet, and outlet of the pelvis were radiographed at each visit, and CT scans were performed. Four observers were recruited to classify the injury type according to the Young-Burgess and Tile classification systems. Interobserver and intraobserver reliability (kappa coefficient, κ) were applied to assess the reproducibility of the two classification systems. A total of 174 patients (21.56%) could not be classified with the Young-Burgess classification, and all patients could be classified according to the Tile system. The mean κ value of the interobserver reliability was 0.558 (range, 0.444 to 0.653) for the Tile classification, indicating moderate agreement, whereas the mean κ value was 0.637 (range, 0.560 to 0.713), indicating substantial agreement, when the Young-Burgess classification was used. The mean κ value for intraobserver reliability was 0.597 (range, 0.567 to 0.653) for the Tile classification and 0.776 (range, 0.748 to 0.803) for the Young-Burgess classification. More pelvic ring injuries could be classified with the Tile classification than could be classified with the Young-Burgess classification. However, the reproducibility of the Young-Burgess classification was greater than that of the Tile classification.